Ectopic pregnancy following levonorgesterol-only emergency contraception: the first Malaysian case report. - Natasha MN; Khoo, HW; Sulaiman, AS; Nur Azurah AG; Md Dali AZH; Jamil MA (Penerbit UKM, 2012)
Levonorgestrel (LNG) is a well-known safe and efficacious emergency contraception (EC). However, ectopic pregnancy following the failure of LNG-only EC has been reported. The exact incidence of ectopic pregnancy has been hindered by lack of data due to the fact that LNG-only EC is accessible at pharmacies without a prescription. We describe a case of ectopic pregnancy in an 18 year-old single woman who took LNG-only EC within 48 hours of unprotected sexual intercourse. She presented to the emergency department at 8 weeks period of amenorrhoea with an acute abdomen and hypovolaemic shock. Laparotomy confirmed a ruptured right tubal pregnancy and salpingectomy was performed. The patient was discharged well after 2 days. We aim to highlight this potential adverse effect and to discuss the plausible causality of ectopic pregnancy following administration of LNG-only EC